Effects of Chemical and Biological Inhibitors of Ethylene on Heat Tolerance in Annual Bluegrass - Sean McBride; William Errickson; Bingru Huang (HortScience)
Heat-stress-induced ethylene accumulation in plants inhibits growth and intensifies damage. Suppressing ethylene production in heat-stressed plants through chemical and biological inhibitors has been effective in promoting heat tolerance in plants. Aminoethoxyvinylglycine (AVG), is a chemical ethylene inhibiter that impedes the ethylene synthesis enzyme 1-aminocyclopropane-1-carboxylic acid (ACC) synthase. Biological ethylene inhibitors include bacteria with ACC deaminase (ACCd) enzyme activity, which suppresses ethylene synthesis by breaking down its precursor, ACC. This study tested two ethylene inhibitors, AVG and a novel strain of the ACCd rhizobacteria Paraburkholderia aspalathi, ‘WSF23’, on annual bluegrass (Poa annua L.) to see whether they are effective in promoting its heat tolerance. P. annua plants were subjected to heat stress conditions for 21 d in controlled-environment growth chambers. Plants were separated into three treatment groups: 1) 25 mL of water (untreated control); 2) 25 mL of 25 µmol AVG; 3) 25 mL of P. aspalathi inoculant suspension. Treatments were applied once before imposing temperature treatments and then every 7 d during 21 d of heat stress. Poa annua treated with either AVG or the P. aspalathi had higher turf quality, green canopy cover, leaf relative water content, and chlorophyll contents during heat stress than the untreated control. Additionally, root characteristics were promoted under heat stress after ethylene inhibitor application, where P. annua treated with AVG had greater root depth and dry weight, while the P. aspalathi treatment resulted in greater total root length. Both ethylene inhibitors improved P. annua performance under heat stress, as characterized by delayed chlorophyll degradation and root maintenance.